2022
DOI: 10.1049/hve2.12191
|View full text |Cite
|
Sign up to set email alerts
|

Interface temperature evolution exposed to arc discharges occurred on the uniform moist pollution layer of composite insulators based on interface fibre Bragg gratings

Abstract: Arc discharges of moist polluted composite insulators pose a serious threat to the stable operation of transmission line. However, there is no effective detection technology for arc discharges. The evolution mechanism of interface temperature accompanied by arc discharges is not clear. In this paper, a 10 kV composite insulator with quasi‐distributed fibre Bragg gratings (FBGs) embedded at the insulator core‐housing interface was developed. The temperature calibration experiment of interface FBGs, and the arc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The grating area thus achieves the function of a filter. The centre wavelength satisfies the following Bragg characteristics [20]:…”
Section: Short-circuit Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The grating area thus achieves the function of a filter. The centre wavelength satisfies the following Bragg characteristics [20]:…”
Section: Short-circuit Testmentioning
confidence: 99%
“…The grating area thus achieves the function of a filter. The centre wavelength satisfies the following Bragg characteristics [20]: λB=2neffΛ ${\lambda }_{\mathrm{B}}=2{n}_{\text{eff}}\Lambda $ where n eff is the effective refractive index of the fibre grating and Λ is the grating period, that is, the distance between two adjacent refractive‐index‐change points.…”
Section: Full‐scale Testmentioning
confidence: 99%
“…This is critical in polluted environments where insulators are susceptible to the high leakage current and discharge activities over their surfaces [144]. Results from dry band arc studies [145][146][147] on insulators with FBG temperature sensors showed a drop in the temperature of the moist polluted composite insulator due to evaporation, followed by rapid increase in temperature during the arc. The arc discharge can therefore be found earlier by using the time point when the temperature begins to drop sharply.…”
Section: Temperaturementioning
confidence: 99%
“…Insulators, which are an essential part of transmission towers, play a vital role, considering that they simultaneously assure both electrical and mechanical reliability [ 3 , 4 ]. In recent years, composite insulators (or polymeric insulators) have become more and more popular in comparison with traditional porcelain and glass insulators due to their excellent hydrophobicity, low weight, and convenience of maintenance [ 5 , 6 ]. For instance, over 10 million strings of composite insulators have already been used at the different levels of high-voltage transmission lines in China [ 7 ].…”
Section: Introductionmentioning
confidence: 99%